PENGARUH LATIHAN IMAGERY EKSTERNAL TERHADAP PENAMPILAN ATLET PENCAK SILAT KATEGORI GANDA DI WILAYAH MALANG RAYA - Naila Eka Oktaviasari; Kurniati Rahayuni (Indonesian Journal of Kinanthropology (IJOK), 2026)
Background: The double category in pencak silat demands strong synchronization, harmony, precision, and consistency of movement between athletes to produce optimal performance. External imagery training is considered a mental training method that can support performance improvement because it helps athletes visualize movements from an observer’s perspective similar to the judging process in the double category. Therefore, this study aims to examine the effect of external imagery training on the performance of double-category pencak silat athletes in the Malang Raya area. The null hypothesis (H0) states that external imagery training has no effect on the athletes’ performance. Methods: The method used in this study is an experiment with a quantitative approach using a pre-test and post-test design on a single group. This study involved 12 pencak silat athletes in the double category as subjects. Results: The treatment of external imagery training has been proven to have an effect on improving the performance of double-category pencak silat athletes. Based on the results of hypothesis testing using the paired samples t-test, a significance value of 0.033 was obtained, which is smaller than 0.05, indicating a significant difference between the pretest and posttest results. These results show that the probability value is smaller than 0.05, so the null hypothesis (H0) is rejected and the alternative hypothesis (H1) is accepted. Thus, it can be concluded that external imagery training has a significant effect on improving the performance of double-category pencak silat athletes after undergoing the training treatment. Conclusions: External imagery practice has a significant effect on improving the performance quality of pencak silat athletes in the doubles category and can be used as a mental training method to help enhance athlete performance in the doubles artistic event.